2019
DOI: 10.2217/bmm-2018-0446
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Homocysteine in the Diagnosis and Prognosis of Coronary Slow Flow Syndrome

Abstract: Aim: To identify the exact molecular markers related to coronary slow flow syndrome (CSFS) and its prognosis. Patients & methods: Data from 54 patients with CSFS diagnosed by coronary angiography and 101 normal control patients were collected and analyzed. Results: Logistic regression analysis confirmed that homocysteine (Hcy; odds ratio: 1.107; 95% CI: 1.018–1.205; p = 0.018) was associated with CSFS. Receiver-operating characteristic curve analysis identified an Hcy value of 17.1 μmol/l as an effective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…23 Demirci et al 16 showed that patients with SCF had significantly higher plasma tHcy levels than those with normal coronary flow. Li et al 14 found HHcy and mean platelet volume to be independent risk factors for SCF in a Chinese Han population. The coronary microvasculature is the dominant gatekeeper for myocardial blood flow below the visible epicardial arteries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23 Demirci et al 16 showed that patients with SCF had significantly higher plasma tHcy levels than those with normal coronary flow. Li et al 14 found HHcy and mean platelet volume to be independent risk factors for SCF in a Chinese Han population. The coronary microvasculature is the dominant gatekeeper for myocardial blood flow below the visible epicardial arteries.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Homocysteine is a sulfur-containing amino acid that functions as a key intermediate in methionine metabolism and hyperhomocysteinemia (HHcy) is well established risk factor for cardiovascular disease. 8 Angiographic findings [9][10][11][12][13][14][15][16] found that patients with SCF had significantly higher plasma total homocysteine (tHcy) levels than those with normal coronary flow and HHcy was strongly correlated with SCF phenomenon in patients without organic coronary stenosis. In addition, HHcy was a potential predictor for SCF prognosis and related to cumulative cardiac events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of CSF still is not clear, and it is mostly considered to be related to coronary atherosclerosis, endothelial dysfunction, chronic inflammatory response, oxidative stress response, microvascular dysfunction, and abnormal platelet function ( Li et al, 2019 ; Henein and Vancheri, 2021 ; Zhu and Su, 2021 ). SXBXP is a modified formula of Su He Xiang Pill derived from Taiping Huimin Heji Ju Fang in the Song Dynasty and it is indicated for the chest painful impediment syndrome with pattern of Qi stagnation and blood stasis.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated homocysteine levels were associated with an increased risk of serious adverse cardio-vascular events and overall mortality among patients with acute coronary syndrome (43). Studies have also shown a positive correlation between hyperhomocysteinemia and the coronary slow flow phenomenon (CSFP) and cardiovascular adverse events (44). Elevated homocysteine levels also represent the independent risk factor for congestive heart failure in adults without myocardial infarction in the history of the disease: the risk was 1.9 times higher in men and 1.8 times higher in women (45).…”
Section: Hyperhomocysteinemia and Cardiovascular Diseasesmentioning
confidence: 99%